Changed into his likeness a biblical theology of personal transformation - Millar, J. Gary (London Apollos, 2021)
"When it comes to the Christian life, what exactly can we expect with regard to personal transformation? In this NSBT volume Gary Millar explores the nature of gospel-shaped change, focusing on "life in the middle"-between the change that is brought about when we become Christians and the final change in which we will be raised with Christ"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Spiritual Formation; Change (Psychology) -- Religious aspects -- Christianity